Which Genes in a Typical Intertidal Seagrass (Zostera japonica) Indicate Copper-, Lead-, and Cadmium Pollution? - Lin, Haiying; Sun, Tao; Zhou, Yi; Gu, Ruiting; Zhang, Xiaomei; Yang, Wei (Frontiers in Plant Science, 2018)
Healthy seagrasses are considered a prime indicator of estuarine and coastal ecosystem function; however, as the only group of flowering plants recolonizing the sea, seagrasses are frequently exposed to anthropogenic heavy metal pollutants, which are associated with high levels of molecular damage. To determine whether biologically relevant concentrations of heavy metals cause systematic alterations in RNA expression patterns, we performed a gene expression study using transcriptome analyses (RNA-seq). We exposed the typical intertidal seagrass Zostera japonica to 0 and 50 μM of copper (Cu), lead (Pb), and cadmium (Cd) under laboratory conditions. A total of 18,266 differentially expressed genes (DEGs) were identified, of which 2001 co-expressed genes directly related by Cu, Pb, and Cd stress. We also examined the effects of short-term heavy metal Cu, Pb, and Cd pulses on the accumulation of metals in Z. japonica and showed metal concentrations were higher in the shoots than in roots. Twelve differentially expressed genes were further analyzed for expression differences using real-time quantitative polymerase chain reaction (RT-qPCR). Our data suggest that as coastal seawater pollution worsens, the sensitive genes identified in this study may be useful biomarkers of sublethal effects and provide fundamental information for Z. japonica resistant gene engineering.